Making case for the continuing existence of sovereign wealth fund in Nigeria (2018)
It is no longer news that the Excess Crude Account established by Chief Olusegun Obasanjo administration in 2004 is today co-existing with the Sovereign Wealth Fund established by Dr. Goodluck Jonathan administration in 2011 pursuant to the enactment of Nigeria Sovereign Investment Authority (Establishment etc) Act. The continued existence of the two accounts have come under intense criticisms and in particular the constitutionality of the two accounts as well as moral and economic justification for withdrawal and expenditures from the accounts since their establishment leading to calls for the discontinuance of the two accounts. While this paper support the calls for closure of Excess Crude Account, it makes case for the continued existence of Sovereign Wealth Fund. The issues which the paper interrogates amongst others are: What are the objectives of Excess Crude Account and Sovereign Wealth Fund? Whether the two accounts are constitutional, or put in another way, what is the legal frameworks for the operation of the two accounts in Nigerian? Is there any justification for the two accounts to co-exist together as part of Nigerian fiscal policy? The paper argues that there is no moral and or economic justification for the co-existence of the two accounts. The paper recommends the closure of the Excess Crude Account with a call for continue existence of the Sovereign Wealth Fund subject to the amendment of enabling statute - Sovereign Investment Authority (Establishment etc) Act - to bring its provisions in conformity with Nigerian Constitutional provisions on the appropriation of the nation funds.